An $O ( ( n\log p )^2 )$ Algorithm for the Continuous p -Center Problem on a Tree - Chandrasekaran, R.; Tamir, A. (SIAM journal on algebraic and discrete methods, 1980)
This paper considers the problem of locating $p$ facilities on a tree network in order to minimize the maximum of the distances of the points on the network to their respective nearest facilities. An $O ( ( n\log p )^2 )$ algorithm for a tree network with $n$ nodes is presented.